(untitled) (ACME, 2024)
These pages are dedicated to an epigraphic study carried out by Margherita Margani on a funerary stela containing an elegiac couplet, preserved in the Museo Archeologico Ibleo. The text of the epitaph, written by a son who devoutly buried his parents in the 6th century B.C., has been the subject of debate since 1942, mainly because of the anthroponyms it contains. Margherita Margani, a secondary school teacher and headmaster in Comiso and Ragusa, was able to conjecture readings that were adopted independently by renowned scholars in later years.